Interventions to reduce suicidal thoughts and behaviours among people in contact with the criminal justice system: A global systematic review. (February 2022) - Carter, Annie; Butler, Amanda; Willoughby, Melissa; Janca, Emilia; Kinner, Stuart A.; Southalan, Louise; Fazel, Seena; Borschmann, Rohan
Summary: Background: People who experience incarceration die by suicide at a higher rate than those who have no prior criminal justice system contact, but little is known about the effectiveness of interventions in other criminal justice settings. We aimed to synthesise evidence regarding the effectiveness of interventions to reduce suicide and suicide-related behaviours among people in contact with the criminal justice system. Methods: We searched Embase, PsycINFO, MEDLINE, and grey literature databases for articles published between 1 January 2000 and 1 June 2021. The protocol was registered with PROSPERO (CRD42020185989). Findings: Thirty-eight studies (36 primary research articles, two grey literature reports) met our inclusion criteria, 23 of which were conducted in adult custodial settings in high-income, Western countries. Four studies were randomised controlled trials. Two-thirds of studies (n=26, 68%) were assessed as medium quality, 11 (29%) were assessed as high quality, and one (3%) was assessed as low quality. Most had considerable methodological limitations and very few interventions had been rigorously evaluated; as such, drawing robust conclusions about the efficacy of interventions was difficult. Interpretation: More high-quality evidence from criminal justice settings other than adult prisons, particularly from low- and middle-income countries, should be considered a priority for future research. Funding: This work was funded by the Australian government's National Suicide Prevention Taskforce. RB is supported by a National Health and Medical Research Council (NHMRC) Emerging Leader Investigator Grant (EL2; GNT2008073). MW is supported by a NHMRC Postgraduate Scholarship (GNT1151103). SF was funded by the NIHR HTA Programme (HTA Project:16/159/09).